2018
DOI: 10.1007/s12031-018-1041-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exosomes Derived from miR-133b Modified MSCs in an Experimental Rat Model of Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) has poor outcomes due to high mortality and morbidity, but until now, the effective treatments remain limited. MicroRNAs (miRNAs) are vital regulators of gene expression and demonstrated to be linked to the pathogenesis of various central nervous system (CNS) diseases. Exosomes are considered as cell-to-cell communication vectors and secreted largely by mesenchymal stromal cells (MSCs). The present study investigated the role of miR-133b delivered by exosomes secreted from MSCs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 39 publications
0
65
0
Order By: Relevance
“…Exosomes are a newly described mechanism of intercellular communication facilitating transfer of miRNAs, lipids, mRNAs, and proteins [36]. Importantly, exosome delivers miRNA or protein to the brain [25,37]. Furthermore, modified exosomes with RVG fused to membrane glycoprotein Lamp2b efficiently delivered miRNA to the brain [34].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are a newly described mechanism of intercellular communication facilitating transfer of miRNAs, lipids, mRNAs, and proteins [36]. Importantly, exosome delivers miRNA or protein to the brain [25,37]. Furthermore, modified exosomes with RVG fused to membrane glycoprotein Lamp2b efficiently delivered miRNA to the brain [34].…”
Section: Discussionmentioning
confidence: 99%
“…[ 193 ] Additionally, EVs from miR‐133b overexpressing MSCs showed an anti‐apoptotic and neuroprotective ability in an intracerebral hemorrhage rat model. [ 194 ] Hypoxia inducible factor (HIF)‐1α overexpression yielded MSC‐CM that enhanced endothelial cell migration, [ 195 ] while HIF‐1α MSC‐EVs enhanced angiogenesis in vitro and in vivo, mediated by EV‐shuttled Jagged 1, [ 196 ] and promoted bone regeneration in a rabbit model of avascular necrosis of the femoral head. [ 197 ] Cartilage tissue regeneration in an osteoarthritis rat model was promoted by delivery of EVs secreted from miR‐140‐5p‐overexpressing MSCs that enhanced cell migration and proliferation.…”
Section: Enhancing the Therapeutic Efficacy Of The Msc Secretomementioning
confidence: 99%
“…These authors also demonstrated that astrocytes treated with exosomes derived from miR-133b-overexpressing MSCs increased neurite branching, and elongation of cortical embryonic rat neurons in vivo [145]. Moreover, exosomes from miR-133b-overexpressing MSCs also suppressed RhoA expression and activated ERK1, ERK2, and CREB in brain tissues in an intracerebral hemorrhage rat model, which resulted in attenuation of apoptosis and neurodegeneration [146]. In other experiments, exosomes from miR-30d-5p-overexpressing MSCs suppressed autophagy by promoting M2 polarization of microglia and macrophages, which reversed brain injury induced by acute ischemic stroke and autophagy in an MCAO mouse model [140].…”
Section: Gene Overexpression To Improve the Function Of Msc-derived Ementioning
confidence: 84%